2018
DOI: 10.1111/pan.13504
|View full text |Cite
|
Sign up to set email alerts
|

Anesthesia in children with osteogenesis imperfecta: Retrospective chart review of 83 patients and 205 anesthetics over 7 years

Abstract: Summary Background Osteogenesis imperfecta is the collective term for a heterogeneous group of connective tissue syndromes characterized by bone fragility with multisystem involvement and perioperative implications. Aims Literature review of anesthetic management of patients with osteogenesis imperfecta revealed a paucity of data on the incidence of perioperative challenges. We sought to determine the rates of these challenges in our study cohort. Methods Data were collected in a specialty orthopedic hospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
1
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 27 publications
3
16
1
3
Order By: Relevance
“…As expected, and similarly to our surgical cohort, the surgical populations described by Hall et al and Rothschild et al had a high incidence of type III OI as type III OI is more severe and often requires more surgery. 10,11 Furthermore, in our study, only nine patients had a positive family history of OI, which differs from the Swedish cohort, where 87% of their cohort had a positive family history and a causative mutation identified. 13 In our study we found a very high incidence (65%) of preoperative anaemia.…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…As expected, and similarly to our surgical cohort, the surgical populations described by Hall et al and Rothschild et al had a high incidence of type III OI as type III OI is more severe and often requires more surgery. 10,11 Furthermore, in our study, only nine patients had a positive family history of OI, which differs from the Swedish cohort, where 87% of their cohort had a positive family history and a causative mutation identified. 13 In our study we found a very high incidence (65%) of preoperative anaemia.…”
Section: Discussioncontrasting
confidence: 79%
“…7 All of these have to be carefully considered before anaesthetising these patients. 10,11 Our study is, to our knowledge, the first study describing management of such cases in a low-middle-income country.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…As a result, patients are prone to fracture above or below the implant because of stress riser formation (70,71). When surgery is indicated, potential challenges with anesthesia should be considered, especially in patients with moderate to severe OI (72).…”
Section: Fracturesmentioning
confidence: 99%
“…Diagnosis is based on clinical presentation, family history, radiographic features and genetic analysis. A 10–30% incidence of bleeding diathesis is reported in patients with OI undergoing surgery 1 . Bleeding may occur despite normal haemostatic tests, making intraoperative bleeding difficult to predict 2 .…”
Section: Id Sex Age (Years) Blood Group Oi Type Isth‐bat Bs Family Inmentioning
confidence: 99%